Asymptotic safety of higher derivative quantum gravity non-minimally coupled with a matter system - Hamada, Yuta; Yamada, Masatoshi (Journal of high energy physics, 2017)
We study asymptotic safety of models of the higher derivative quantum gravity with and without matter. The beta functions are derived by utilizing the functional renormalization group, and non-trivial ﬁxed points are found. It turns out that all couplings in gravity sector, namely the cosmological constant, the Newton constant, and the R2 and Rµ2ν coupling constants, are relevant in case of higher derivative pure gravity. For the Higgs-Yukawa model non-minimal coupled with higher derivative gravity, we ﬁnd a stable ﬁxed point at which the scalar-quartic and the Yukawa coupling constants become relevant. The relevant Yukawa coupling is crucial to realize the ﬁnite value of the Yukawa coupling constants in the standard model.